Drinking game participation among college students: Gender and ethnic implications - Pedersen, Eric R. (Addict Behav, 2006)
Participation in drinking games by college students has recently sparked research attention. While previous research indicates that women play drinking games at lower frequencies than men, the current study reveals that college women may be playing games at rates similar to college men. In a sample of 105 coed college students, participants completed a 3-month Timeline Followback recording every drinking event and quantity consumed. They then were prompted to identify which drinking events involved drinking games and how much alcohol was consumed during game playing. Both men and women engaged in drinking games at similar rates and consumed more drinks on game playing days than on non-game drinking days. However, drinking game participation was related to alcohol-related consequences in women only. Further, while Caucasian participants played drinking games more often than non-Caucasian participants, an association between game participation and alcohol-related consequences emerged in non-Caucasian participants.